Relationship Between Job Burnout and Organizational Climate in Nurses Working in Teaching Hospitals Affiliated to Iran University of Medical Sciences - Daryadokht Masror Roudsary; Zahra Salehi; Hamid Haghani (Iran University of Medical Sciences, 2022)
Background & Aims: Job burnout can leads absenteeism, leaving the job or having the intention to leave, reduced quality of life, reduced performance, and reduced quality of patient care and commitment to the organization. Organizational climate has always been important in the nursing profession and in the hospital environment where the nurse' performance is known as an important component in improving the quality of treatment. This study aims to determine the relationship of job burnout with organizational climate in nurses. Materials & Methods: This descriptive correlational study with cross-sectional design was performed in 2020 in the internal surgical wards of four teaching hospitals affiliated to Iran University of Medical Sciences. The sampling was done by a cluster sampling method. The sample size was determined 200 at a 95% confidence level and considering a 80% test power. To collect data, a demographic form, the Maslach burnout inventory, and Halpin and Croft's organizational climate description questionnaire were used. Data analysis was performed in SPSS v. 24 software using descriptive and inferential statistics. Results: Emotional exhaustion domain of job burnout had a statistically significant correlation with all dimensions of organizational climate except for group spirit and disengagement; it had a negative significant correlation with the hindrance dimension and a positive significant correlation with other dimensions. With the increase of organizational climate, emotional exhaustion increases, resulting in more job burnout. Conclusion: Health workers, especially nurses and managers, should take measures to reduce job burnout and improve organizational climate and patient satisfaction according to the existing conditions and resources. It is recommended that the educational supervisors of the hospitals develop and implement in-service training focusing on the components of job burnout and organizational climate.